Work-Related Musculoskeletal Disorders and Job Instability Among Nursing Professionals: A Comprehensive Analysis - Nawaf Salih Hasan AL WBBI, Awad Dakhel Mauyof, Rawaf Faleh Alanazi, Nahar Hamdan Alanazi, Nasser Yahya Ali Ghallah, Faisal Abdulaziz Alhamid, Mohammed Obaid Eid Alanazi, Taghreed Obaid Eid Alanazi (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
The nature of nursing work within hospital units exposes professionals to various risk factors that may contribute to work instability and the development of work-related musculoskeletal disorders (WMSDs), leading to illness and varying levels of work incapacity.Objectives: This study aims to investigate the relationship between work instability among nursing professionals and the occurrence of WMSDs.Methods: A descriptive cross-sectional study with a quantitative approach was conducted . The Nurse-Work Instability Scale and the Nordic Musculoskeletal Questionnaire were used to assess nursing professionals working in adult and pediatric intensive care units, as well as orthopedic, neurosurgery, and head/neck surgery units.Results: A total of 111 nursing professionals participated in the study, with 25.2% showing low risk of work instability, 44.1% medium risk, and 30.6% high risk. Statistical analyses revealed significant associations between work instability and variables such as work sectors (p = 0.004) and specific WMSDs in various body regions: neck (p = 0.001), shoulders (p = 0.000), upper back (p = 0.007), elbow (p = 0.005), wrist (p = 0.002), lower back (p = 0.046), hip/thighs (p = 0.006), knees (p = 0.021), and ankles/feet (p = 0.011).Conclusions: This study demonstrates a clear association between work instability and the presence of WMSDs among nursing professionals. It underscores the importance of implementing interventions to address work instability, which can precede disability and is closely linked to absenteeism and early retirement.